A study of brand loyalty of Apple products in Malaysia - Lew, Yoke Peng (2022)
The main objective of conducting this research project is to investigate the factors that affect consumer brand loyalty to Apple products in Malaysia. Thus, there have various variables were examined such as brand awareness, perceived quality, perceived value, brand personality, brand associations, and brand uniqueness will bring impact on consumer brand loyalty to Apple product users. Quantitative method approach is used, and 200 survey questionnaires are distributed to Malaysian who are Apple product users by using convenient sampling technique. All 200 survey are softcopy and distributed to target respondents through Google form. By using Statistical Package for Social Science (SPSS), data that collected from the survey questionnaire are able to analyze. The results acquired from the SPSS shows that there is significant relationship between all independent variable towards the dependent variable. However, the variables which are perceived quality and brand association shown insignificant relationship towards the brand loyalty of Apple product users. The research also mentioned about the limitations during the progress of research project and recommendation are offered for the future researchers.